The need for contemporary understanding of the Qur’an: considering scientific method (al-manhaj al-'ilmi) - Ushama, Thameem (Kulliyyah of Science, IIUM, 2011)
Realizing the need for contemporary understanding of the Qur’an by exploring scientific method or approach, the paper analyzes issues with regard to Qur’an’s inimitable ellipticism. It highlights some of the aspects of the inimitable features of the Text including the views of some Muslim scholars with regard to the use of scientific method and deals with a discourse on contemporary scholars’ criticism of the scientific inimitable features of the Qur’an. It examines conservative, contemporary, moderate and modernist approaches of interpreting passages relating to signs of the universe (al-ayat al-kawniyyah) along with brief justifications articulated by both proponents and opponents. It recommends the most appropriate approach or method to have contemporary understanding of the Qur’an.